2014
DOI: 10.4172/2329-9029.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Circulating Testosterone: Impact of Herbal Dietary Supplements

Abstract: Low circulating testosterone levels can present numerous problems related to the overall health and well-being of individuals, men in particular. This finding is well-documented in the literature and low testosterone appears more prevalent in older men, in particular those who are physically inactive and who present with elevated levels of body fat. Multiple botanical (herbal) products have been claimed to elevate circulating testosterone in men; however, data pertaining to the use of such herbal preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…In an animal model, EL induces testosterone synthesis due to concomitant increases in LH and FSH (Low, Choi, et al., 2013). While in the same study, the reduction in oestrogen level is speculated to be due to inhibition of aromatase by a specific compound in EL such as eurycomanone, reducing the conversion of testosterone to oestrogen (Gunnel & Bloomer, 2014; Low, Choi, et al., 2013). Studies have shown that an increase in testosterone activates the negative feedback loop on the HPG axis, which subsequently reduces testosterone production and maintains homeostasis through inhibition of LH and FSH (McLachlan et al., 2002; Weinbauer & Nieschlag, 1993).…”
Section: Discussionmentioning
confidence: 90%
“…In an animal model, EL induces testosterone synthesis due to concomitant increases in LH and FSH (Low, Choi, et al., 2013). While in the same study, the reduction in oestrogen level is speculated to be due to inhibition of aromatase by a specific compound in EL such as eurycomanone, reducing the conversion of testosterone to oestrogen (Gunnel & Bloomer, 2014; Low, Choi, et al., 2013). Studies have shown that an increase in testosterone activates the negative feedback loop on the HPG axis, which subsequently reduces testosterone production and maintains homeostasis through inhibition of LH and FSH (McLachlan et al., 2002; Weinbauer & Nieschlag, 1993).…”
Section: Discussionmentioning
confidence: 90%
“…A multitude of herbal products claims to potentially increase testosterone, of which Eurycoma longifolia (EL) has shown promising effects in increasing the testosterone concentrations ( 18 ). EL has been used as a traditional medicine for its aphrodisiac effects and treatment of intermittent fever (malaria) ( 19 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…This is on account of all men have an enzyme called aromatase that converts testosterone to a shape of estrogen. Taking a medication to hinder the transformation of testosterone to estrogen additionally is certifiably not a smart thought [15][16][17][18].…”
Section: Low Testosterone Levelsmentioning
confidence: 99%